Analisis Kasus Wanprestasi Melalui Kaidah Fiqh Qadha’ - Muhammad Jamaluddin; Muhammad Defri; Muhammad Hegel Mucthohari; Lisnawati Lisnawati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the application of qawāʿid al-fiqhiyyah (Islamic legal maxims) in the field of fiqh qaḍāʾ, focusing on judicial and procedural aspects within the Islamic legal system. The study explains the definition, scope, and significance of qawāʿid al-fiqhiyyah as general principles that serve as the foundation for decision-making in the resolution of disputes in Islamic courts. It highlights six main elements in Islamic judiciary: the judge (qadhi), the law, mahkum bihi, mahkum ‘alaihi, mahkum lahu, and legal sources, and examines several key maxims, such as the necessity to accept a judge’s ruling in cases of ijtihad, the status of a judge’s order in the use of property, the role of evidence and oaths in judicial proceedings, and the distinction between confession and evidence in legal proof. Through an analysis of these maxims, the article emphasizes that the application of qawāʿid al-fiqhiyyah is crucial for ensuring justice, legal certainty, and public benefit in Islamic judicial practice. These findings are expected to serve as a reference for the development of Islamic procedural law that is adaptive and responsive to the needs of modern society.